PENERAPAN MODEL PROBLEM BASE LEARNING BERBASIS MEDIA WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V MATA PELAJARAN IPAS - Enengwitri Ginasihan; Sandi Budi Iriawan; Iman Indrayana (ADISAM PUBLISHER, 2025)
Improving the quality of learning is one of the main focuses in the world of education, especially in the current digital era. The problem of student learning outcomes is one of the educational challenges that educators need to pay attention to. This study aims to determine the effectiveness of the Wordwall media-based Problem Based Learning (PBL) model in improving the learning outcomes of grade V students in Natural and Social Sciences (IPAS) subjects at SD Negeri 178 Gegerkalong KPAD. The method used is Classroom Action Research (PTK) with a McTaggart cycle design, consisting of two cycles. The results of the study showed a significant improvement in student learning outcomes. In the first cycle, the learning completeness increased from 15.38% in the pretest to 46.15% in the post test. In the second cycle, the learning completeness increased even more to 88.46%. These findings show that the implementation of Wordwall-based PBL is effective in improving learning outcomes and student engagement in learning. This study recommends the use of PBL with the support of digital technology to improve the quality of learning in elementary schools